2019
DOI: 10.3389/fpsyg.2019.01114
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs in “Brilliance” and Belonging Uncertainty in Male and Female STEM Students

Abstract: A wide-spread stereotype that influences women’s paths into STEM (or non-STEM) fields is the implicit association of science and mathematics with “male” and with requiring high levels of male-associated “brilliance.” Recent research on such “field-specific ability beliefs” has shown that a high emphasis on brilliance in a specific field goes along with a low share of female students among its graduates. A possible mediating mechanisms between cultural expectations and stereotypes on the one hand, and women’s u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 22 publications
1
41
0
Order By: Relevance
“…Consistent with this, Lewis and Hodges (2015) found that the degree of intellectual fit—the subjective sense that one possesses the same abilities, skills, and knowledge as one’s peers—predicts motivations and intentions to persist academically among undergraduates enrolled in psychology and linguistics courses (note that they refer to low levels of ability belonging as “ability belonging uncertainty”). pSTEM students were not examined in this past research, but the heavy emphasis within many pSTEM fields on inherent genius and natural talent is well documented (Leslie et al, 2015; Meyer et al, 2015; Ito and McPherson, 2018; Deiglmayr et al, 2019) and likely makes intellectual fit particularly relevant within pSTEM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this, Lewis and Hodges (2015) found that the degree of intellectual fit—the subjective sense that one possesses the same abilities, skills, and knowledge as one’s peers—predicts motivations and intentions to persist academically among undergraduates enrolled in psychology and linguistics courses (note that they refer to low levels of ability belonging as “ability belonging uncertainty”). pSTEM students were not examined in this past research, but the heavy emphasis within many pSTEM fields on inherent genius and natural talent is well documented (Leslie et al, 2015; Meyer et al, 2015; Ito and McPherson, 2018; Deiglmayr et al, 2019) and likely makes intellectual fit particularly relevant within pSTEM.…”
Section: Introductionmentioning
confidence: 99%
“…Just as women may be more prone to scan their environment and daily experiences for examples of whether they socially belong (Cheryan et al, 2009), they may also be more attuned to experiences confirming or denying whether they intellectually belong. In addition, recent research shows that female pSTEM majors more strongly believe that their fields require innate brilliance than their male peers do (Deiglmayr et al, 2019). This greater expectation that brilliance is required may make women more sensitive to their subjective assessments of ability fit than men.…”
Section: Introductionmentioning
confidence: 99%
“…This is also the case in college, where feeling that one belongs there based on one's own ability in the field predicts women's intention of remaining in the field (Banchefsky et al, 2019). As the associated ability beliefs in a field are correlated with belonging (Deiglmayr et al, 2019), researching belonging in different social environments is especially important to understand the formation of career choices. Deiglmayr et al (2019) showed that females in mathematics and physics had higher beliefs that promote brilliance or talent as the determinant of success -domains in which women also report more uncertainty of belonging.…”
Section: Sense Of Belonging In Educational Settingsmentioning
confidence: 98%
“…As the associated ability beliefs in a field are correlated with belonging (Deiglmayr et al, 2019), researching belonging in different social environments is especially important to understand the formation of career choices. Deiglmayr et al (2019) showed that females in mathematics and physics had higher beliefs that promote brilliance or talent as the determinant of success -domains in which women also report more uncertainty of belonging. Students' ability beliefs are also associated with the actual gender ratio in a field, meaning that fewer women in a field and higher beliefs about need of brilliance to succeed are connected (Bailey et al, 2019).…”
Section: Sense Of Belonging In Educational Settingsmentioning
confidence: 99%
“…Similarly, women earn half or more of all associate’s, bachelor’s, master’s, and doctoral degrees but are less well represented in STEM fields, with gains in specific areas but major disparities remaining in others (Cimpian et al, 2020; National Science Board, National Science Foundation, 2019). Much research has been done on the belief in “brilliance” and gender representation in various STEM fields (e.g., Deiglmayr et al, 2019), and proportionally more men are represented in disciplines perceived as requiring more raw brilliance and intelligence (Leslie et al, 2015). But in physics, engineering, and computer science, college majors in which males outnumber females by 4-to-1, researchers find only high-achieving women pursuing these subjects, while low- and average-achieving men are well represented (Cimpian et al, 2020).…”
mentioning
confidence: 99%